(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the clinical, radiological and functional results of patients treated with different methods in our clinic for proximal humerus fracture. Material and Methods: A total of 106 patients with a diagnosis of proximal humerus fracture, who were scheduled for treatment, received management and followed up periodically after discharge were included. Patient files, X-RAY radiographs in the PACS system, surgical notes and outpatient epicrisis were used. Functional results were evaluated according to Constant shoulder score at the last visit.Results: The mean age of the patients was 53.6 years (17-94). The mean follow-up period was 11.3 months (6-40 months). 55 (51.9%) had Type II, 35 (33%) had Type III and 16 (15.1%) had Type IV proximal end humeral fractures. As a result of the evaluation performed at the last follow-up of the patients, Constant-Murley’s total score was 64.50 out of 100 (31-88). Score distribution according to Neer classification of patients; A Constant-Murley score median with a Neer Type II fracture was 74.00 (36-88), a Constant-Murley Score median with a Neer Type III fracture was 61.00 (31-78), and a Constant-Murley score median with a Neer Type IV fracture was 44.50 (33-70). Conclusion: When the fracture type and functional outcome of the patients were compared, functional outcome decreased as the fracture type increased. Young patients had better functional results than older patients.